2007
DOI: 10.1007/s00264-007-0492-9
|View full text |Cite
|
Sign up to set email alerts
|

An 8- to 10-year review of the Rotaglide total knee replacement

Abstract: Mobile-bearing knee arthroplasty (MBKA) is an alternative to fixed-bearing knee arthroplasty. This was a retrospective study of the Rotaglide Total Knee System. We present the results of the monitoring of 77 patients (85 knees) with a median duration to failure or end of follow up of 8.5 years (range 0.4 to 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Although there is a difference in the revision rates between the two groups (cemented group 2 % and hybrid group 4.9 %), with cemented group having lower rate, the statistical analysis showed no significance in the difference (n.s.). The revision rate of the entire cohort was 3.3 %, similar to that of other studies [13,14,19]. There were no cases of mobile meniscus implant dislocation and no evidence during the follow-up period and also in the last examination of soft tissue impingement.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although there is a difference in the revision rates between the two groups (cemented group 2 % and hybrid group 4.9 %), with cemented group having lower rate, the statistical analysis showed no significance in the difference (n.s.). The revision rate of the entire cohort was 3.3 %, similar to that of other studies [13,14,19]. There were no cases of mobile meniscus implant dislocation and no evidence during the follow-up period and also in the last examination of soft tissue impingement.…”
Section: Discussionsupporting
confidence: 86%
“…The shape of the femoral component increases the contact area between the two components throughout flexion [24]. The high congruency between the polyethylene and the femoral and tibial components minimizes the amount of debris from polyethylene wear, which has been associated with bone lysis [13]. The femoral and the tibial components can be fixated with or without cement [24].…”
Section: Introductionmentioning
confidence: 99%
“…Hudd et al [15] also reported no revision in a series of 357 Rotaglide knees, but only 150 attended for follow-up 5-8 years after operation. Horwitz et al [16] reported on 85 Rotaglide knees with a mean follow-up of 8.5 years (range: 0.4-10.1); there were 6 revisions, none of which for aseptic loosening. Wilson et al [17] also reported no aseptic loosening with the Rotaglide in a series of 71 knees with follow-up between 5 and 8.2 years.…”
Section: Discussionmentioning
confidence: 99%
“…The Rotaglide Total Knee Arthroplasty was introduced into clinical practice in 1988. It was the first Total knee implant which used a mobile polyethylene fully conforming insert which glided and slide on top of a highly polished tibial component Although there are several reports in the literature regarding long term clinical results of this prosthesis [12][13][14][15][16][17][18][19], to our knowledge there are no studies describing wear patterns of its fully conforming mobile PE insert. Evaluation of wear on the retrieved Polyethylene inserts in knee prostheses has generated a great amount of work since the beginning of the eighties, because these observations have led to a better understanding of the wear mechanisms.…”
Section: Introductionmentioning
confidence: 99%